2021
DOI: 10.1021/acsami.0c19404
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Energy-Level Alignment Effects Determine Substituent-Tuned Single-Molecule Conductance

Abstract: The rational design of single molecule electrical components requires a deep and predictive understanding of structure-function relationships. Here we explore the relationship between chemical substituents and the conductance of metal-single molecule-metal junctions, using functionalized oligophenylenevinylenes as a model system. Using a combination of mechanically controlled break-junction experiments and various levels of theory including non-equilibrium Green's functions, we demonstrate that the connection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 56 publications
2
17
1
Order By: Relevance
“…Importantly, both experiments and theory demonstrate the image potential contribution to ε h to be ∼0.1 eV per contact for OPX, which translates to approximately 25–30% of the total magnitude of ε h for complete, two-contact junctions. Note that this significant effect differs slightly from previous findings in which the image charge in single molecule junctions was found to dominate the energy level alignment. ,, Our results do not contradict the earlier findings, but rather indicate that image charge effects are system-specific and depend on the size and orientation of molecules with respect to the metal electrodes, as well as the electrode shape and total number of electrodes (up to 3 if there is a gate).…”
Section: Introductioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Importantly, both experiments and theory demonstrate the image potential contribution to ε h to be ∼0.1 eV per contact for OPX, which translates to approximately 25–30% of the total magnitude of ε h for complete, two-contact junctions. Note that this significant effect differs slightly from previous findings in which the image charge in single molecule junctions was found to dominate the energy level alignment. ,, Our results do not contradict the earlier findings, but rather indicate that image charge effects are system-specific and depend on the size and orientation of molecules with respect to the metal electrodes, as well as the electrode shape and total number of electrodes (up to 3 if there is a gate).…”
Section: Introductioncontrasting
confidence: 84%
“…Given that the total energy level offset ε h trans is ∼0.6 eV, eV image is clearly important as each contact provides ∼−0.08 eV, meaning that the total contribution of eV image to ε h trans is ∼−0.16 eV or 25% of the total offset from E f . One can say that image charge effects are a significant factorthough not the dominant factorin overall energy alignment in OPX junctions. ,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Since then, the performance of molecular diodes, This helped regulate single-molecule conductance. [12] Venkataraman et al showed that the dominant conducting orbitals for thiophene/thiophene-1,1-dioxide oligomers of an equal length can be tuned by varying the electron affinity of the units incorporated into the backbone. [13] Koch et al and Zojer et al have demonstrated the importance of molecular modification for tuning charge transport in organic electronics from the sophisticated study of spectroscopy [14] and theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%